2006
DOI: 10.1111/j.1467-842x.2006.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in colorectal cancer mortality by ethnicity and socio‐economic position in New Zealand, 1981‐99: one country, many stories

Abstract: Background:Ethnicity and socio‐economic position are important determinants of colorectal cancer (CRC) mortality. In this paper, we determine trends in colorectal cancer mortality by ethnicity and socioeconomic position in New Zealand. Methods:Cohort studies of the entire New Zealand population for 1981‐84, 1986‐89, 1991‐94 and 1996‐99 (linking Census and mortality datasets) allowed direct determination of trends in CRC mortality by income and education. For ethnicity, we used routine unlinked Census and mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Schiffman (1988), discounted Caldararo's central proposal where sitting down (squatting) allowed the passage of more fecal matter in his small sample, but verified Caldararo's theory that this behavior would result in more fecapentane excretion and thus less exposure to mutagenic activity. This would be consistent with recent findings, including Shaw et al (2006). This is especially likely given the failure to find a dietary explanation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Schiffman (1988), discounted Caldararo's central proposal where sitting down (squatting) allowed the passage of more fecal matter in his small sample, but verified Caldararo's theory that this behavior would result in more fecapentane excretion and thus less exposure to mutagenic activity. This would be consistent with recent findings, including Shaw et al (2006). This is especially likely given the failure to find a dietary explanation.…”
Section: Resultssupporting
confidence: 92%
“…One element that is absent from the review is how behavior may affect fecal water pH and the time exposure of colon tissue to its components. Shaw, et al (2006) recently published a paper on colorectal cancers in New Zealand. Caldararo (1988) did some fieldwork in Polynesia in the 1980s and tried to understand the low rates of colorectal cancers reported then by physicians in the Maori population (e.g., Smith, et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicated a significant association between low SES and poorer cancer survival in Western countries, Australasia and Japan [9][10][11][12][13][14], while the contribution of specific causes to differences in mortality has been found to vary between countries. In recent years, at least three studies from the U.S. reported a poorer survival of pancreatic M A N U S C R I P T…”
Section: Discussionmentioning
confidence: 99%
“…New Zealand has a particularly high incidence and mortality from colorectal cancer 14. Age-adjusted incidence is lower in Maori compared with non-Maori populations (nine compared with 15 per 100 000),2 but mortalities are now similar, having decreased in non-Maori and increased in Maori over time 11 15 16…”
Section: Introductionmentioning
confidence: 99%